Synthesis of HfB2 powders by mechanically activated borothermal reduction of HfCl4 - Akçamlı, Nazlı; Agaogullari, Duygu; Balci, Ozge; Ovecoglu, M. Lutfi; Duman, Ismail (Elsevier Sci Ltd, 2016)
HfB2 powders were synthesized via a borothermal reduction route from mechanically activated HfCl4 and B powder blends. Mechanical activation of the powder blends was carried out for 1 h in a high-energy ball mill using hardened steel vial and balls. Mechanically activated powders were subsequently annealed at 1100 degrees C for 1 h under Ar atmosphere. Then, purification processes such as washing with distilled water and leaching in HCl solution were applied for the elimination of the undesired boron oxide (B2O3) phase and the probable Fe impurity. The effect of boron amount on the microstructure of the resultant powders was investigated. The boron amount in the starting blends plays an important role in the formation of the HfO2 phase. HfB2 powders without any detectable HfO2 were prepared by adding 20 wt% excess amount of boron. Microstructural analyses of the mechanically activated, annealed and purified powders were performed using X-ray diffractometer (XRD), particle size analyzer (PSA), stereomicroscope (SM), scanning electron microscope/energy dispersive spectrometer (SEM/EDS) and transmission electron microscope (TEM). (C) 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Hafnium diboride; Hafnium tetrachloride; Borothermal reduction; Mechanical activation; Purification